2012
DOI: 10.1007/s10518-012-9349-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of low velocity alluvial deposits influencing seismically-induced shear strains: the Grottaperfetta valley test-site (Rome, Italy)

Abstract: The presence of peats and high compressibility inorganic clays within alluvial fills on the left-side tributaries of the Tiber River, close to Rome's historic center in Italy, is well documented in literature. Nevertheless, few literature data exist until now on the dynamic properties of these deposits by undisturbed bore-hole samples. The Galba test-site was set up to characterise dynamic properties of the alluvial deposits by using lab-tests as well as to derive velocity profiles by seismic noise measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(49 reference statements)
1
5
1
Order By: Relevance
“…The here obtained Vs profile ( Fig. 2a) is largely in agreement with other literature data (Bozzano et al, 2008;Caserta et al, 2012) but points out a different value for the AL-VSC deposits (i.e. Vs value according to literature is 180 m/s, instead the value deduced from our analysis is 350 m/s) and a velocity gradient in the clay and silt deposits of the Santa Cecilia Formation (PT-CS), i.e.…”
Section: Calibration Of the Seismo-stratigraphic Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…The here obtained Vs profile ( Fig. 2a) is largely in agreement with other literature data (Bozzano et al, 2008;Caserta et al, 2012) but points out a different value for the AL-VSC deposits (i.e. Vs value according to literature is 180 m/s, instead the value deduced from our analysis is 350 m/s) and a velocity gradient in the clay and silt deposits of the Santa Cecilia Formation (PT-CS), i.e.…”
Section: Calibration Of the Seismo-stratigraphic Modelsupporting
confidence: 91%
“…Vs value according to literature is 180 m/s, instead the value deduced from our analysis is 350 m/s) and a velocity gradient in the clay and silt deposits of the Santa Cecilia Formation (PT-CS), i.e. corresponding to a Vs linear increment, according to Bozzano et al (2008) and Caserta et al (2012), from about 500 m/s up to 1100 m/s.…”
Section: Calibration Of the Seismo-stratigraphic Modelcontrasting
confidence: 41%
“…From a general point of view, for unconventional and historical structures like the Colosseum, the simplified approach suggested by the NTC08 for soil classification is not adequate and specific studies are needed to build a truly representative model of the subsoil and the buried part of the structure. Bozzano et al [2000], Bozzano et al [2008] and Caserta et al [2012] investigated the different lithotypes constituting the recent sedimentary fill of the Holocene Tiber River Valley under both static and dynamic conditions. Bianchi Fasani et al [2013] reported the typical ranges of shear-wave velocities observed in situ for the pyroclastic units within Rome city.…”
Section: Site Description and Geological Backgroundmentioning
confidence: 99%
“…A wide-ranging database was compiled in the current study from the previously published laboratory tests (U.S. Army Corps of Engineers, 1978Engineers, , 1979Kokusho et al, 1982;Borden et al, 1994Borden et al, , 1996Lanzo et al, 1997;S&ME Inc., 1993, 1998Stokoe et al, 1995;Caserta et al, 2012). These studies include numerous tests conducted on cohesive soils to measure their dynamic properties at low and large strain levels using resonant column, simple shear, cyclic torsional shear, and cyclic triaxial tests.…”
Section: Data Collectionmentioning
confidence: 99%